Development of KARIN (Indonesian Youth Work) Application on Student Creativity - Tri Wahyuni; Muhhibin, Ahmad; Sumardjoko, Bambang (Perspektif Ilmu Pendidikan, 2023)
This study aims to form a creative dimension in students by using the KARIN application (Indonesian Youth Work). This application is expected to be able to form a creative dimension in students. The KARIN application (Indonesian Youth Work) is an android application that functions to channel students' ideas by writing simple articles. This application has 4 screens, namely the Main Screen which contains instructions for using and starting the application. The second screen is the main screen which displays two options, namely the copyright of the work and the collection of works. The third screen, when students select copyrighted works, they will be transferred to select copyrighted works, namely students write what they want to write. The last screen contains a collection of works, students can see the results from one friend to another. This study uses the R&D method using the 4D approach which is condensed into 3D. The tests carried out in this study were media tests and application effectiveness tests. The media test gets a score of 81 with a very valid category. The effectiveness test got a score of 67.52, this value is included in the good category.